Creative non-fiction in dementia: Men's experiences of sport-focused reminiscence using narrative methods. (December 2021) - Sass, Cara; Surr, Claire; Lozano-Sufrategui, Lorena
Abstract: Qualitative research methodologies offer valuable insight into important aspects of the lived experience of dementia, and provide inclusion opportunities for those with moderate to severe cognitive impairment. Narrative methods such as creative non-fiction (CNF) offer an evocative method to utilise direct accounts of the experience of living with dementia, to attenuate professionals and academics to best practice approaches to supporting their needs. Men face unique challenges in finding appropriate support to help them to maintain a sense of identity following a diagnosis of dementia. Yet, academic literature seldom uses the voices of those affected when highlighting this issue. This study presents ethnographic data written as a composite narrative using CNF, to explore how social connections are formed through a structured sports-based reminiscence intervention for men living with dementia. This article demonstrates how the CNF approach can be applied to ethnographic data, offering a detailed description of the writing process applied in this study. In particular, we discuss in detail the ways in which CNF writing techniques have helped to enhance the communication of key mechanisms observed during fieldwork.